PROBLEM BASED LEARNING AS AN EFFORT TO IMPROVE 21ST CENTURY CRITICAL THINKING SKILLS IN ELEMENTARY EDUCATION - Septianto Saleh, Yusuf Yusian; Fauziah, Kurniatun Nailatin (PGMI UNHASY, 2026)
In the 21st century, it is necessary to update and improve learning methods for students. The problem-based learning method is a relevant and effective method to be applied in learning in basic education. This is then supported by basic critical thinking skills which focus students on being able to understand and find solutions to the learning problems found. The aim of this research is to describe and explain problem-based learning in an effort to improve 21st century critical thinking in basic education. The research method used is a literature study which explores information and data from various books, journals and articles related to the research which is then presented and analyzed according to the research objectives. The research results show that problem-based learning has a close relationship with the development of critical thinking skills. Through this learning, students are not only invited to think creatively and analytically, but also to solve problems collaboratively and effectively.